Mediation In English-Persian News Translation: A Critical Discourse Analysis Approach - Daghigh, Ali Jalalian (2015)
This thesis looks at mediation of ideology in the translation of news from English to Persian within the socio-political context of Iran. The study seeks to achieve the following objectives: a) to investigate the influence of the socio-political context of Iran in mediation in news translation; b) to explore the manipulative procedures which are involved in this mediation; and c) to investigate the appropriateness of Critical Discourse Analysis (CDA) models in acconunodating the analysis of mediation in news translation. Theoretically, the study benefits from van Dijk's CDA (1998, 2005) as well as ideas from the Descriptive Translation Studies paradigm. Methodologically, the research is enriched by combining the linguistic toolkits of different CDA approaches. The corpus of the study consists of 31 English opinion articles published mainly by the Western news institutions and their Persian translation by Iranian Diplomacy, an Iranian govenunental news portal. The results reveal a number of findings. First, the socio-political factors governing news translation in Iran are manifested as a re-contextualized translation, which represents the ideology of the power holders. Second, the manipulations are exerted by two main strategies of emphasizing the desired representations of the source texts and deemphasizing the undesired ones. There are also four subcategories of strategies involved, i.e., blocking, downgrading, maintaining and intensifying. Third, the four subcategories are evident through the application of specific manipulative purpose-based procedures in the translated discourse. Finally, a model is proposed through modifying van Dijk's monolingual CDA which could moderately explain mediation in news translation at both macro and micro levels of analysis.